2013
DOI: 10.3399/bjgp13x667169
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing depression severity using the UK Quality and Outcomes Framework depression indicators: a systematic review

Abstract: BackgroundDepression is a major cause of chronic ill-health and is managed in primary care. Indicators on depression severity assessment were introduced into the UK Quality and Outcomes Framework (QOF) in 2006 and 2009. QOF is a pay-forperformance scheme and indicators should have evidence to support their use; potential unintended consequences should also have been considered. AimTo review the effectiveness of routine assessment of depression severity using structured tools in primary care, and to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Practices which elected to code a higher proportion of patients with depression are likely to have engaged in more assertive follow up of patients to complete these and it is possible that this led to continued treatment. While these indicators have recently been withdrawn because of a lack of evidence of effectiveness, 25 the results of this study suggest that incentivising assertive followup alone may have improved treatment for patients with depression.…”
Section: Implications For Practicementioning
confidence: 95%
“…Practices which elected to code a higher proportion of patients with depression are likely to have engaged in more assertive follow up of patients to complete these and it is possible that this led to continued treatment. While these indicators have recently been withdrawn because of a lack of evidence of effectiveness, 25 the results of this study suggest that incentivising assertive followup alone may have improved treatment for patients with depression.…”
Section: Implications For Practicementioning
confidence: 95%
“…However this does not always confer benefit on our patients. The systematic review by Shaw and colleagues published in this issue 10 concludes that the introduction of clinical performance indicators in the UK for assessing depression severity has had little impact on GP management of depression, or on subsequent remission or treatment response.…”
Section: Perspectivesmentioning
confidence: 99%
“…19 A systematic review of primary care in the United Kingdom found no evidence that assessing depression severity using a structured tool and subsequent treatment based on that assessment resulted in better outcomes. 33 Organizations promoting depression screening, such as Medicare, should consider integrating incentives for screening and high-leverage activities 34 (e.g., care coordination, team-based care). For older adults, especially those with multimorbidity, choosing measures that may meet their preferences may be a better goal than widespread screening, 35 especially if, as found in the current study, a large proportion of repeated screening is being conducted in individuals who are not reporting symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%